Stranded nations? Transition risks and opportunities towards a clean economy. (1st April 2023) - Andres, Pia; Mealy, Penny; Handler, Nils; Fankhauser, Samuel
Abstract: The transition away from a fossil-fuel powered economy towards a cleaner production system will create winners and losers in the global trade system. We compile a list of 'brown' traded products whose use is highly likely to decline if the world is to mitigate climate change, and explore which countries are most at risk of seeing their productive capabilities 'stranded'. Using methods from economic geography and complexity, we develop novel measures of transition risk that capture the extent to which countries' export profiles are locked-in to brown products. We show that countries exporting a high number of brown products, especially technologically sophisticated ones, could find it relatively easy to transition. Conversely, countries with exports highly concentrated in a few, low-complexity brown products have much fewer nearby diversification opportunities. Our results suggest that export complexity and diversity play a key role in determining transition risk. Path-breaking diversification strategies are needed to prevent nations from becoming stranded.